2014
DOI: 10.2337/db13-1210
|View full text |Cite
|
Sign up to set email alerts
|

Deficiency in Type I Interferon Signaling Prevents the Early Interferon–Induced Gene Signature in Pancreatic Islets but Not Type 1 Diabetes in NOD Mice

Abstract: Type I interferons (IFNs) have been implicated in the initiation of islet autoimmunity and development of type 1 diabetes. To directly test their involvement, we generated NOD mice deficient in type I IFN receptors (NOD.IFNAR1 2/2). Expression of the type I IFN-induced genes Mx1, Isg15, Ifit1, Oas1a, and Cxcr4 was detectable in NOD islets as early as 1 week of age. Of these five genes, expression of Isg15, Ifit1, Oas1a, and Mx1 peaked at 3-4 weeks of age, corresponding with an increase in Ifna mRNA, declined a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
34
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 33 publications
(40 citation statements)
references
References 26 publications
5
34
1
Order By: Relevance
“…In our colony, the first detectable upregulation of interferon genes was Ifnb1 at 4 weeks followed by Ifna at 6 weeks and Ifng at 8 weeks. Other groups have reported the upregulation of type I interferons in both the pancreatic lymph nodes and islets of NOD mice during the 3-4 week time period, although the timing seems to vary between colonies (86-87). …”
Section: The Early Events In Islets: the Interferon Signaturementioning
confidence: 94%
See 1 more Smart Citation
“…In our colony, the first detectable upregulation of interferon genes was Ifnb1 at 4 weeks followed by Ifna at 6 weeks and Ifng at 8 weeks. Other groups have reported the upregulation of type I interferons in both the pancreatic lymph nodes and islets of NOD mice during the 3-4 week time period, although the timing seems to vary between colonies (86-87). …”
Section: The Early Events In Islets: the Interferon Signaturementioning
confidence: 94%
“…This issue remains very confusing to the field. Neutralization of the type I interferon receptor with antibodies decreased diabetes incidence, but genetic ablation of the receptor had no effect (87). Removal of the type II interferon receptor had no effect in one study and led to a reduction of diabetes in females and an increase in diabetes in males in another (88, 89).…”
Section: The Early Events In Islets: the Interferon Signaturementioning
confidence: 99%
“…Transient blockade of either the type I interferon receptor or expression of Ifn-α by dendritic cells before the onset of insulitis markedly decreases the incidence of diabetes mellitus in NOD mice 94,95 . By contrast, NOD mice lacking a functional type I interferon receptor develop diabetes mellitus at the same rate as wild-type NOD mice 96 . A possible interpretation of these apparently contradictory findings is that viral infection and the subsequent production of type I interferons favours autoimmunity (and eventually T1DM) if the expression of interferons is induced at early and critical points during the development of this condition.…”
Section: Candidate Genesmentioning
confidence: 95%
“…Further, recent data have also shown that mice with elevated expression of MDA5 exhibit increased systemic autoimmune disease (13,14). However, although identification of IFN I transcriptional signatures and increased IFN I expression has implicated a role for IFN I in diabetes in mice, loss of IFN I signaling did not affect diabetes induction (15). This implies that the IFN I signature itself is not causal to the disease process; rather, the signature reflects an ongoing and underlying causal process, i.e., virus infection.…”
mentioning
confidence: 92%